Relationship between interlimb asymmetries and speed and change of direction speed in youth handball players - Madruga-Parera, M.; Bishop, C.; Beato, M.; Fort-Vanmeerhaeghe, A.; Gonzalo-Skok, O.; Romero-Rodríguez, D. (The Journal of Strength and Conditioning Research, 2021)
The aims of the present study were to quantify interlimb asymmetry from jumping, change of direction speed (CODS), and iso-inertial tests and to establish the association between those asymmetry scores and performance during speed and CODS tests in youth handball athletes. Twenty-six youth handball players (age: 16.2 ± 0.9 years) volunteered to participate in this study and performed single-leg countermovement jumps, single-leg broad jumps, single-leg lateral jumps, CODS tests at 180° (CODS180) and 90° (CODS90), change of direction actions with iso-inertial overload (crossover step [CRO] and lateral shuffle step), and a 20-m sprint test. Excellent intraclass correlation coefficient (ICC) values were found for all tests (ICC = 0.96-1.00) with the exception of the dominant limb during the CODS90 test (ICC = 0.69). Interlimb asymmetry scores ranged from 3.66 to 12.67%. Iso-inertial asymmetry values were higher than those found during jumping tasks (9.8-12.7% vs. 3.66-8.76%). Spearman's r correlations showed significant relationships between CRO asymmetry and CODS90 performance on both limbs (r = 0.48-0.51; p < 0.05) and CODS180 (r = 0.41-0.51; p < 0.05) and a sprint test (r = 0.46; p < 0.05). These results show the test-specific nature of asymmetries in youth handball players, with iso-inertial device and CODS deficit presenting the greatest magnitude of asymmetries. Furthermore, interlimb differences during iso-inertial device (CRO) were associated with reduced CODS and sprint performance. These results suggest that the use of iso-inertial devices for the detection of interlimb asymmetry may be more effective than the total time during traditional CODS tests and that larger imbalances are associated with reduced athletic performance in youth handball players.